2017
DOI: 10.14502/tekstilec2017.60.235-242
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Fabric Performance for Car Seats

Abstract: This paper deals with the investigation of the performance of car seat fabrics in terms of physiological comfort of sitting, specifi cally their water vapour resistance and air permeability. The current work presents an alternative approach to increasing the eff ectiveness of car seat fabrics through a combination of newly designed middle layer with forced convection achieved by a supplementary suction ventilation device. The supplementary device was designed to measure water vapour permeability by means of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The theoretical warp density was 28 threads/cm (14+14 for top and bottom) and the theoretical weft density was 34 picks/cm for The comfort is the first criterion that values the customer, specifically psychological comfort-makes reference to the esthetic aspects-and physiological comfort captured by the view and touch. Thermo-physiological comfort is not just a pleasant feeling while sitting as it improves the performance and concentration of drivers [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical warp density was 28 threads/cm (14+14 for top and bottom) and the theoretical weft density was 34 picks/cm for The comfort is the first criterion that values the customer, specifically psychological comfort-makes reference to the esthetic aspects-and physiological comfort captured by the view and touch. Thermo-physiological comfort is not just a pleasant feeling while sitting as it improves the performance and concentration of drivers [9].…”
Section: Methodsmentioning
confidence: 99%
“…Havelka et.al investigated the performance of car seat fabrics in terms of physiological comfort of sitting, specifically the water vapor resistance and air permeability properties were determined and presented an alternative approach to increase the effectiveness of car seat fabrics through a combination of newly designed middle layer with forced convection achieved by a supplementary suction ventilation device. The results showed that water vapor transport was increased by approximately 20% compared to the standard way of measurement by means of SGHP because of forced air flow in the plane of ribbedchanneled structure in the middle layer of car seat [9]. In a study, the relationship between abrasion and tensile strength properties of automobile seat fabrics was examined.…”
Section: Methodsmentioning
confidence: 99%